Pengaruh Media Alat Bantu terhadap Keterampilan Passing Bawah Bolavoli pada Pembelajaran PJOK - Mohammad Zaim Zen; Ilmul Ma’arif; Rendra Wahyu Pradana; Guntum Budi Prasetyo (SPRINTER: Jurnal Ilmu Olahraga, 2025)
This study aims to obtain information related to the effect of media tools on volleyball underhand passing. The method used is experimental research with a one-group pre-test post-test design, with a sample size of 65 students from junior high schools selected using purposive sampling. The procedure involved conducting a pre-test, treatment, post-test, and assessment of underhand passing using a modified Braddy Volley Ball Test. Data analysis was conducted using descriptive statistics and a paired T-test using SPSS calculations. The pre-test results fell into the poor category (46.16%). The post-test results fell into the good category (41.53%). Meanwhile, the difference test results showed that there was an effect on underhand passing skills based on the sig results. The conclusion is that teaching aids have a positive impact on volleyball underhand passing.